PENGARUH PEMBERIAN CORNMEAL DAN CORNMEAL-SOY TERHADAP KADAR KOLESTEROL DALAM SERUM TIKUS - Harti, Leny Budhi; Rudijanto, Achmad; Kristianto, Yohanes (Jurnal Kedokteran Brawijaya, 2008)
Coronary  Heart  Diseases  (CHD)  are  a  serious  health  problem  that  commonly  occur  not  only  in  modern countries, but aslo  in developing countries like  Indonesia. The high cholesterol level in  blood is  a risk factor that  may  cause  CHD  by  atherosclerosis  mecanism.  dietary  fiber  may  be  used  to  prevent  atherosclerosis. Cornmeal and cornmeal-soy are products of corn, that rich in fiber. This research was aimed to study about the  effect  of  cornmeal  and  cornmeal-soy  on  serum  cholesterol  level  of  6-8  mounths  male  wistar  rats.  The subjects  are  25  male  wistar  rats.  These  mice  will  be  provided  into  five  groups.  (1)  gruop  that  given atherogenic  diet  only,  (2)  gruop  that  given  atherogenic  diet  with  cornmeal  3.4  g/day,  (3)  gruop  that  given atherogenic diet with cornmeal 6.8 g/day, (4) gruop that given atherogenic diet with cornmeal-soy 3.6 g/day, (5)  gruop  that  given  atherogenic  diet  with  cornmeal-soy  7.2  g/day.  Data  collecting  include  first  weight,  last weight,  weight  gain,  nutrient  intake,  and  serum  lipid.  Statistic  analysis  that  be  used  is  ANOVA  one  way. Results showed that  wistar rats which given atherogenic diet with cornmeal and cornmeal-soy  had trend to increase  cholesterol  and  LDL  level.  According  to  statistic  analysis,  cholesterol  and  LDL  level  among  groups were not significant (p > 0.05). However wistar rats which given atherogenic with cornmeal and cornmeal-soy in  high  doses,